Selection of High Producers From Combinatorial Libraries for the Production of Recombinant Proteins in Escherichia coli and Vibrio natriegens - Eichmann, Joel; Oberpaul, Markus; Weidner, Tobias; Gerlach, Doreen; Czermak, Peter (Frontiers in Bioengineering and Biotechnology, 2019)
The optimization of recombinant protein production in bacteria is an important stage of process development, especially for difficult-to-express proteins that are particularly sensitive or recalcitrant. The optimal expression level must be neither too low, which would limit yields, nor too high, which would promote the formation of insoluble inclusion bodies. Expression can be optimized by testing different combinations of elements such as ribosome binding sites and N-terminal affinity tags, but the rate of protein synthesis is strongly dependent on mRNA secondary structures so the combined effects of these elements must be taken into account. This substantially increases the complexity of high-throughput expression screening. To address this limitation, we generated libraries of constructs systematically combining different ribosome binding sites, N-terminal affinity tags, and periplasmic translocation sequences representing two secretion pathways. Each construct also contained a green fluorescent protein tag to allow the identification of high producers and a thrombin cleavage site enabling the removal of fusion tags. To achieve proof of principle, we generated libraries of 200 different combinations of elements for the expression of an antimicrobial peptide, an antifungal peptide, and the enzyme urate oxidase (uricase) in Escherichia coli and Vibrio natriegens. High producers for all three difficult-to-express products were enriched by fluorescence-activated cell sorting. Our results indicated that the E. coli ssYahJ secretion signal is recognized in V. natriegens and efficiently mediates translocation to the periplasm. Our combinatorial library approach therefore allows the cross-species direct selection of high-producer clones for difficult-to-express proteins by systematically evaluating the combined impact of multiple construct elements.